Pre-amplification as a method for improvement of quantitative RT-PCR analysis of circulating miRNAs - Sekovanić, Ankica (Array, 2021)
Introduction: The assessment of circulating miRNAs is challenging and still limited due to their low concentrations, small size and lack of referencevalues in human biological samples. Pre-amplification of complementary DNAs may facilitate reliable miRNA quantification. The aim of our studywas to evaluate the efficacy of pre-amplification as a step to increase the sensitivity of qPCR analysis for five candidate circulating miRNAs presumablyrelated to toxic metals and cigarette smoke exposure: miR-1537, miR-190b, miR-16, miR-21, and miR-146a.Materials and methods: Candidate miRNAs expression was analysed in plasma samples of 19 mother-newborn pairs. For isolation, transcription,pre-amplification and qPCR quantification kits and protocols by Qiagen (Hilden, Germany) were used. Paired t-test or Wilcoxon rank test were usedto compare miRNAs expression levels with and without a pre-amplification step prior to qPCR, separately in maternal and cord plasma. Intraclasscorrelation (ICC) was calculated as an agreement measure between procedures for each miRNA.Results: Pre-amplification facilitated the detection of all assayed miRNAs with an overall cycle threshold (CT) improvement of 6.6 ± 0.89 (P <0.05).Excellent ICCs (>0.90) were found between data for preamplified and not preamplified miR-16, miR-21 and miR-146a. However, these correlationsfor low expressed miR-190b were moderate (0.79 in maternal; 0.61 in cord plasma) and poor for miR-1537 (0.49 in maternal; no correlation in cordplasma).Conclusion: Pre-amplification is a useful, necessary step in the analysis of miR-1537 and miR-190b as a reliable procedure facilitating extracellularmiRNA expression detection in human plasma by real-time PCR quantification.